2006
DOI: 10.1159/000095302
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Potentised Substances on Growth Kinetics of Saccharomyces cerevisiae and Schizosaccharomyces pombe

Abstract: Homeopathic potencies are used as specific remedies in complementary medicine. Since the mode of action is unknown, the presumed specificity is discussed controversially. Objective: This study investigated the effects of potentised substances on two yeast species, Saccharomyces cerevisiae and Schizosaccharomyces pombe, in a stable and reliable test system with systematic negative controls. Materials and Methods: Yeast cells were cultivated in either potentised substances or water controls in microplates and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…In opposition to the popularity of homeopathy in several countries, most of the clinical trials and meta-analyses of clinical trials performed so far have indicated either lack of efficacy of homeopathic preparations in healing patients or merely a tendency towards efficacy [6][7][8][9]. At the experimental level, some studies performed with animals [10,11], plants [12] or in vitro [13,14] revealed that homeopathic dilutions may exert biological effects.…”
Section: Introductionmentioning
confidence: 99%
“…In opposition to the popularity of homeopathy in several countries, most of the clinical trials and meta-analyses of clinical trials performed so far have indicated either lack of efficacy of homeopathic preparations in healing patients or merely a tendency towards efficacy [6][7][8][9]. At the experimental level, some studies performed with animals [10,11], plants [12] or in vitro [13,14] revealed that homeopathic dilutions may exert biological effects.…”
Section: Introductionmentioning
confidence: 99%
“…the effect that some potentized substances did affect the measured parameters, whilst others did not when tested in the same experimental set-up, was observed for viruses (Glatthaar-Saalmüller et al, 2001), yeast (Scherr et al, 2006) and fungi (Khanna and Chandra, 1992). Another phenomenon was demonstrated in those studies in which several potency levels were tested simultaneously: there were active and inactive potency levels.…”
Section: Models Based On Healthy Plants Microorganisms and Virusesmentioning
confidence: 79%
“…Among the studies with microorganisms most often yeasts have been used as model organisms (Steffen, 1984(Steffen, , 1985Baker and Smith, 1985;Hagelberg, 1987;Koch and Partilla, 1995;Engstler, 2004;Scherr et al, 2006). Some of these works were inspired by the positive results of Jones et al (Jones and Jenkins, 1983a,b) indicating sensitive reactions of Saccharomyces cerevisiae to potencies of Pulsatilla.…”
Section: Models Based On Healthy Plants Microorganisms and Virusesmentioning
confidence: 99%
See 2 more Smart Citations